Community College Faculty Perceptions of the Quality Matters™ Rubric - Gregory, Rhonda L.; Rockinson-Szapkiw, Amanda J.; Cook, Vickie S. (Online Learning, 2020)
This paper reviewed the factors that make up quality assurance including course design, content, delivery, and institutional support, as well as infrastructure in relationship to professional development impact on teaching practice. Building on the assumption identified in literature is the concept of course design being the most critical component impacting both student learning and faculty teaching. Course design affects student learning, faculty satisfaction with the course, establishes a teaching presence, and influences the transactional difference that occurs between the students and the instructor. Using the premise of the critical nature of course design, this study reviewed how the use of faculty professional development through a Applying the Quality Matters Rubric (APPQMR) workshop using the Quality Matters (QM) rubric as a framework to impact course design created specific faculty perceptions and affected teaching practice. Six themes identified from the research related to faculty’s perceived value and rigor of the QM rubric and training are discussed in the conclusion section.